2022
DOI: 10.21037/jgo-22-454
|View full text |Cite
|
Sign up to set email alerts
|

Survival and prognostic factors for postoperative primary appendiceal cancer: a retrospective cohort study based on the Surveillance, Epidemiology, and End Results database

Abstract: Background: The factors affecting the postoperative survival of patients with primary appendiceal cancer (PAC) have yet to be fully explored. And there are no clear guidelines for adjuvant treatment after appendectomy. Whether chemotherapy can prolong patient survival after appendectomy, is critical in guiding postoperative medications. The majority of studies on appendiceal cancer are single case reports, and they focused on the incidence of appendiceal cancer. The present study aimed to investigate the survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In addition, Hispanic individuals had improved survival compared with non-Hispanics, which has been previously reported in CRC but is a novel finding for appendiceal cancer 3 24. Similar to previous studies, we found SRCC had worse survival than both MAC and NMAC while MAC was associated with lower mortality compared with NMAC 1 10. Not surprisingly, advanced tumour stage and grade exhibited higher mortality rates, while surgical intervention was associated with improved survival.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, Hispanic individuals had improved survival compared with non-Hispanics, which has been previously reported in CRC but is a novel finding for appendiceal cancer 3 24. Similar to previous studies, we found SRCC had worse survival than both MAC and NMAC while MAC was associated with lower mortality compared with NMAC 1 10. Not surprisingly, advanced tumour stage and grade exhibited higher mortality rates, while surgical intervention was associated with improved survival.…”
Section: Discussionsupporting
confidence: 88%
“…Although appendiceal malignancies are rare, their incidence in the USA has steadily increased in the past two decades to 1–2 per million person-years despite stable rates of appendectomies 1–3. Previous large population-based studies have identified key demographic and clinical prognostic factors associated with survival in patients with appendiceal malignancies, including age, race, marital status, histological type, tumour stage, tumour grade, lymph node resection, chemotherapy and surgical intervention 1 4–10. These variables have been used to construct prognostic nomograms that predict overall mortality and disease-specific survival 11 12…”
Section: Introductionmentioning
confidence: 99%
“…Patients with low-grade tumors had a favorable prognosis. Patients with distant metastases did not experience a prolonged survival benefit from CTH [ 6 ]. Fleischmann et al evaluated the role of regional lymph node (RLN) retrieval on stage migration, OS, and cancer-specific survival (CSS) in appendiceal cancer.…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…The incidence of appendix cancer of primary origin (PAC) is estimated to be 1.2–1.63 per 100,000 people in the United States [ 5 , 6 ]. The 5-year overall survival (OS) depends on the histologic type of the PAC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation